2022
DOI: 10.3390/diagnostics12092051
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Growth Differentiation Factor 15 in COVID-19: A Corollary Subjective Effect or Not?

Abstract: Coronavirus disease 2019 (COVID-19) is primarily caused by various forms of severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) variants. COVID-19 is characterized by hyperinflammation, oxidative stress, multi-organ injury (MOI)-like acute lung injury (ALI) and acute respiratory distress syndrome (ARDS). Different biomarkers are used in the assessment of COVID-19 severity including D-dimer, ferritin, lactate dehydrogenase (LDH), and hypoxia-inducible factor (HIF). Interestingly, growth differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 99 publications
0
37
0
Order By: Relevance
“…As well, the design of these studies may limit the detection of cognitive dysfunction in patients with cardiovascular diseases [ 50 , 52 ]. Notably, a population-based study from the Mayo Clinic Study of Aging involving 1160 patients for assessment of neuroimaging biomarkers in AD patients aged more than 65 years with a history of cardiovascular complications on statins pharmacotherapy showed no significant correlation between long-term statins and tau/amyloid burden [ 121 , 122 ]. This finding proposed that statins pharmacotherapy had neutral effects on AD pathogenesis.…”
Section: Statins and Admentioning
confidence: 99%
“…As well, the design of these studies may limit the detection of cognitive dysfunction in patients with cardiovascular diseases [ 50 , 52 ]. Notably, a population-based study from the Mayo Clinic Study of Aging involving 1160 patients for assessment of neuroimaging biomarkers in AD patients aged more than 65 years with a history of cardiovascular complications on statins pharmacotherapy showed no significant correlation between long-term statins and tau/amyloid burden [ 121 , 122 ]. This finding proposed that statins pharmacotherapy had neutral effects on AD pathogenesis.…”
Section: Statins and Admentioning
confidence: 99%
“…ACE2 is highly distributed and expressed in many organs, including the intestine, kidney, lung, brain, heart, testis, and some immune cells [ 8 , 9 ]. Severe SARS-CoV-2 infection induces an exaggeration of immune response and release of pro-inflammatory cytokines with the progression of hypercytokinemia and cytokine storm [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…They act through the activities of their pro-apoptotic and anti-apoptotic products, thereby serving as indicators of the success or failure of apoptosis. Several studies revealed the high expression of the tumor-suppressor protein p53, followed by the accumulation of the pro-apoptotic protein Bax, which activated the intrinsic pathway of apoptosis [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%